Average DMF-T Index and Performed Treatment Index (PTI) Achievement of Class X High School Students in Tangerang City - Pudentiana Rr. R. E.; Tauchid, Siti Nurbayani; Fadjeri, Indrayati; Anggreni, Eka; Ngatemi; Fathur (International Journal of Science and Society, 2024)
The escalating prevalence of dental caries and other oral diseases in Indonesia underscores the urgency of targeted health promotion, particularly among school students who represent a critical demographic for such interventions. Recent findings from the National Basic Health Research (Riskesdas) highlight a concerning rise in dental caries, signaling a need for comprehensive strategies to curb this trend and improve oral health outcomes. This research aimed to measure the average DMF-T Index and achievement of the Performed Treatment Index (PTI) in class X high school students in Tangerang City. The research design used is to research a situation objectively to solve or answer the problems being faced in the current situation. The population in this study was class The data collection method is by examining the teeth that have these components using instruments, recording forms, and other equipment. The data analysis used in this research is an analysis of two variables. The results of this study found that the average permanent dental caries experience index (DMF-T) of respondents in this study was 2.32. This means that on average there are 2 to 3 teeth per person with tooth decay, while the indicators for achieving healthy teeth determined by WHO for the age category over 12 years include DMF-T ≤ 3. This shows that the average DMF-T index of respondents includes good criteria. The Performed Treatment Index (PTI) or a person's effort to maintain permanent teeth for class X students at Tangerang State High School was 11.11%; referring to the indicators and targets for achieving healthy teeth determined by WHO, including Good PTI if ≥ 50% and this shows that the respondent's PTI achievement rate includes poor criteria.